Pseurotin D Induces Apoptosis through Targeting Redox Sensitive Pathways in Human Lymphoid Leukemia Cells - Mosejová, Eva; Bosnjakovic, Rebeka; Kubala, Lukáš; Vašíček, Ondřej (Antioxidants (Basel, Switzerland), 2021)
Chronic lymphocytic leukemia (CLL) is the most prevalent lymphoid malignancy in many geographical regions of the world. Pseurotin D, a secondary metabolite of fungi, represents a group of bioactive natural products with a newly ascribed range of interesting biological activities. The purpose of this study was to bring new insights into the mechanism behind the effects of pseurotin D on MEC-1 cells as a representative CLL cell line, with a particular focus on selected signaling pathways important in the proliferation of cells and targeting mitochondrial metabolism. Our results showed that pseurotin D was able to significantly inhibit the proliferation of MEC-1 cells and arrested them in the G2/M cell cycle phase. In addition, pseurotin D was able to induce apoptosis. We found that all of these effects were associated with a change in mitochondrial membrane potential and the production of mitochondrial reactive oxygen species (ROS). We showed for the first time that pseurotin D suppresses MEC-1 cell proliferation and induces apoptotic cell death via induction of the collapse of the mitochondria respiratory chain and the ROS-related caspase pathway. Our results show the pseurotins family as promising compounds which could serve as a basis for the development of new compounds in the treatment of lymphoma.
Keywords: reactive oxygen species; mitochondrial activity; proliferation; lymphoma; pseurotin D; apoptosis